ID: 263. Issue 1 (November 2015) - Pencik, Jan; Schlederer, Michaela; Gruber, Wolfgang; Unger, Christine; Walker, Steven M.; Chalaris, Athena; Marié, Isabelle; Hassler, Melanie R.; Javaheri, Tahereh; Aksoy, Osman; Blayney, Jaine K.; Mazal, Peter; et al.
<x xml:space="preserve">Abstract</x> Prostate cancer (PCa) is one of the most frequently diagnosed forms of cancer in men. The majority of newly diagnosed PCa are non-aggressive and it remains a clinical challenge to distinguish these from lethal cancers. Hyperactive IL-6/Stat3 signalling is thought to be an important driving force in PCa. However, targeting of the IL-6/Stat3 axis in PCa patients failed to elicit therapeutic benefit. Here, we tested the hypothesised oncogenic role of IL-6/Stat3 in PCa progression. Surprisingly, we find that genetic inactivation of IL-6 or Stat3 dramatically promotes PCa cancer progression leading to widespread metastasis formation. Mechanically, IL-6/Stat3 signaling activates p19ARF-triggered senescence and directly regulates ARF-MDM2-p53 axis. Intriguingly, in vivo blocking of IL-6/STAT3 signalling by the JAK1/2 inhibitor ruxolitinib in human LNCaP xenografts showed significantly enhanced tumour size and weight. The ruxolitinib-treated xenografts also had markedly increased numbers of Ki-67+ cancer cells accompanied by a decrease in STAT3 and p14ARF expression. In human biopsies and metastatic specimens, we find massive loss of Stat3 and p14ARF expression, the human homologue of murine p19ARF, significantly correlating our findings with a high risk of disease recurrence. These findings identify STAT3 and ARF as powerful markers (potential biomarkers) to stratify high from low-risk PCa patients. Our findings of IL-6/STAT3-regulated ARF tumour suppressive pathway point to risk of anti-IL-6 inhibition as therapy in metastatic prostate cancer.